Relationship between distributive justice, procedural justice, conflict management styles and affective commitment: a study among bank employees in Northern Malaysia - Muhammad Asyraf Mohd Kassim; Hazril Izwar Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2016)
This paper aims to elucidate the relationship of distributive and procedural justice on affective commitment through conflict management styles and examine the mediating effect of conflict management styles between distributive and procedural justice and affective commitment. Self-administered questionnaires were delivered to 330 respondents throughout Northern Malaysia. Next, the data were analyzed using statistical analysis of SPSS and Partial Least Squares of Structural Equation Modelling (PLS-SEM). Results showed that distributive and procedural justice was positively related to integrating, obliging and compromising styles while negatively related to dominating style but not related to avoiding style. It also revealed that integrating, obliging and compromising styles were positively significant with affective commitment while dominating style was negatively significant with affective commitment but avoiding style does not relate with affective commitment. In conclusion, the results also showed conflict management styles fully mediate the relationship between distributive and procedural justice and affective commitment.